Product Development of a Rollator Walker for the Elderly Based on Kansei Engineering to Explore Users Emotional Preferences in Supporting Independence and Improving Quality of Life - Araminta, Calyca Didy; Tranggono, Tranggono; Islami, Mega Cattleya Prameswari Anissa (Academia Open, 2026)
General Background The Indonesian population is undergoing a demographic shift toward an aging structure, leading to increased health risks and mobility limitations among the elderly. Specific Background Falls among the elderly frequently result in injuries that compromise independence, self-confidence, and overall quality of life, necessitating effective mobility aids such as rollator walkers. Knowledge Gap Current academic literature in Indonesia predominantly focuses on wheelchair development, with a notable absence of research on rollator walkers that integrate functional requirements with the specific emotional preferences of elderly users. Aims This study seeks to develop a rollator walker product design that addresses the functional and emotional needs of elderly residents at the Hargo Dedali Nursing Home. Results Utilizing Kansei Engineering and conjoint analysis, the research identified 13 critical Kansei Words—such as sturdy, lightweight, and comfortable—which were translated into design specifications. The optimized design features an iron frame, pneumatic wheels, and a firm seat base. The Marginal Homogeneity Stuart-Maxwell test confirmed no significant difference between the developed design and the elderly residents’ emotional requirements. Novelty This study employs a specialized mapping between subjective Kansei emotional preferences and objective technical design attributes to create a mobility aid that minimizes fall risks while maintaining user practicality. Implications These findings demonstrate the effectiveness of Kansei Engineering in mobility aid development, providing a structured framework for designing functional products that support independence and improve the psychological well-being of the elderly population. Highlights: Emotional preferences for mobility aids were categorized into agility, comfort, and affirmation factors. Integration of Kansei Engineering successfully translates subjective user sentiments into objective physical design attributes. Statistical validation confirms the developed design aligns with the mobility and independence requirements of elderly users. Keywords: Developed Product, Elderly, Emotional Preferences, Kansei Engineering, Rollator Walker